2012
DOI: 10.1074/jbc.m112.395921
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conformation-dependent Prion Protein Epitopes

Abstract: Background: Despite structural reorganization during disease, conformational prion protein epitopes remain undefined. Results: We identify specific amino acids constituting novel conformational monoclonal antibody epitopes. Conclusion: Immunoreactivities of globular domain epitopes depend on maintenance of regional tertiary structure. Significance: Our studies address how denatured conformational epitopes remain functional, provide insights into normal and disease-related prion protein, and expand epitope tagg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…For serial PMCA, 6 μL of amplified material was diluted into 54 μL of fresh normal brain homogenate. Western blots were developed using anti-PrP mAbs 6H4 (Prionics AG) or PRC5 (32).…”
Section: Methodsmentioning
confidence: 99%
“…For serial PMCA, 6 μL of amplified material was diluted into 54 μL of fresh normal brain homogenate. Western blots were developed using anti-PrP mAbs 6H4 (Prionics AG) or PRC5 (32).…”
Section: Methodsmentioning
confidence: 99%
“…PMCA reactions were performed as described previously (32) at a seed to substrate ratio of 1:4,000, digested with PK at a final concentration of 0.33 μg/μL, and analyzed by Western blotting using anti-PrP mAb 6H4 (Prionics AG) or PRC5 (61).…”
Section: Methodsmentioning
confidence: 99%
“…23 Likewise human, bank vole, or mouse PrP C expressing RK13 transfectants also failed to propagate certain prion isolates. 13,24 The ability of RK13 cells to propagate prions upon expression of exogenous PrP C from multiple species 12,13,16,17 clearly confirmed that RK13 cells have the required cellular machinery for efficient prion propagation. Although PRNP haplotype 3 and 4 caprine scrapie inocula were able to produce clinical scrapie in recipient goats 9 and Tg338 mice 21 which was very similar to PRNP haplotype 1 and 2 caprine scrapie inoculated animals, the lack of scrapie prion propagation in cpRK13cells when inoculated with the same PRNP haplotypes 3 and 4 scrapie inocula highlight the possible involvement of other unidentified factors to establish successful infection.…”
Section: Cprk13 Cells Support Propagation Of Classical Caprine Scrapimentioning
confidence: 82%
“…12,13,16,17 PCR amplified caprine PRNP haplotype 2 was cloned into a mammalian expression plasmid (pIRESpuro3-cp) (Fig. S1A).…”
Section: Resultsmentioning
confidence: 99%